Idiopathic Sclerosing Encapsulating Peritonitis: A Rare Cause of Subacute Intestinal Obstruction - Mei Chin Lim; Niketa Chandrakant Chotai; Danilo Medina Giron (Case Reports in Medicine)
We present a case of a previously healthy 50-year-old gentleman who had recurrent vomiting and abdominal pain of two-month duration. The patient was subsequently diagnosed with abdominal cocoon on computed tomography. Idiopathic sclerosing encapsulating peritonitis, also known as abdominal cocoon, is a rare cause of small bowel obstruction. Visualization of variable encasement of the small bowel loops by a characteristic membranous sac, either preoperatively with cross-sectional imaging or intraoperatively, is the key to diagnosis. This is a highly treatable condition; surgical excision of the sac with adhesiolysis facilitates a full recovery in affected patients.